Chaotic Behavior of Traffic-Flow Evolution with Two Departure Intervals in Two-Link Transportation Network. (6th November 2018) - Liu, Shixu; Guo, Lidan; Easa, Said M.; Chen, Wensi; Yan, Hao; Tang, Yingnuo
Abstract : In this study, the influence of traveler's departure time choice in day-to-day dynamic evolution of traffic flow in a transportation network is investigated. Combining historical information and real-time information, a dynamic evolution model of traffic flow with a study period divided into two intervals is proposed for a simple two-link network. Then, the evolution of network traffic flow is investigated using numerical experiments. Three types of information are considered: ( 1 ) only historical information, ( 2 ) only real-time information, and ( 3 ) both historical and real-time information. The results show that the dynamic evolution of network traffic flow under the three types of information is similar. However, the possibility of chaos occurrence under both historical and real-time information is smaller than that under two individual types of information. When chaos occurs, the chaotic behavior in traffic-flow evolution under only real-time information is relatively less complex than that under the other two types of information.